The Chinese Children and Families Cohort Study: The Nutrition, Physical Activity, and Ultraviolet Radiation Data Collection. Issue 3 (May 2018) - Potischman, Nancy; Fang, Liwen; Hao, Ling; Bailey, Regan R.; Berrigan, David; Berry, Robert John; Brodie, Alison; Chao, Ann; Chen, Jing; Dodd, Kevin; Feng, Yajing; Ma, Guansheng; et al.
Abstract : This article reports the study design, methodological issues and early results of a pilot study testing methods for collecting nutrition, physical activity, and ultraviolet (UV) radiation exposure data in a groundbreaking study in China. Epidemiological studies suggest that exposures across the entire life course, including in utero, early childhood, and adolescence, may be important in the etiology of adult cancers and other chronic diseases. The Chinese Children and Families Cohort Study intends to follow-up subjects from the 1993 to 1995 Community Intervention Program of folic acid supplementation for the prevention of neural tube defects. This cohort is unique in that only folic acid exposure during pregnancy varies between groups as other supplements were not available, and there were nutrient deficiencies in the populations. Prior to launching a large-scale follow-up effort, a pilot study was conducted to assess the feasibility of recontacting original study participants to collect extensive diet, physical activity, and UV radiation exposure data in this population. The pilot study included 92 mothers and 184 adolescent children aged 14 to 17 years from 1 urban and 1 rural Community Intervention Program site. Subjects completed a Food Frequency Questionnaire, a 3-day food record, a physical activity questionnaire, a 3-day sun exposure diary together with 3 days of personal UV dosimetry, and 7 days of pedometry measurements and provided blood, saliva, and toenail samples. Grip strength and body composition measurements were taken, and ambient solar UV radiation was monitored in both study sites. While most of the assessments were successful, future studies would likely require different dietary intake instruments. The purpose of this report is to describe the study design and methodological issues emerging from this pilot work relevant for the follow-up of this large birth cohort.